Growth of wafer-scale graphene–hexagonal boron nitride vertical heterostructures with clear interfaces for obtaining atomically thin electrical analogs. Issue 11 (2nd March 2022) - Yang, Huihui; Wang, Gang; Guo, Yanming; Wang, Lifeng; Tan, Biying; Zhang, Shichao; Zhang, Xin; Zhang, Jia; Shuai, Yong; Lin, Junhao; Jia, Dechang; Hu, PingAn
Abstract : Wafer-scale vertical hexagonal boron nitride/graphene heterostructures with clear interfaces are realized via a two-step metallic alloy assisted epitaxial growth method. Abstract : Two-dimensional (2D) integrated circuits based on graphene (Gr) heterostructures have emerged as next-generation electronic devices. However, it is still challenging to produce high-quality and large-area Gr/hexagonal boron nitride ( h -BN) vertical heterostructures with clear interfaces and precise layer control. In this work, a two-step metallic alloy-assisted epitaxial growth approach has been demonstrated for producing wafer-scale vertical hexagonal boron nitride/graphene ( h -BN/Gr) heterostructures with clear interfaces. The heterostructures maintain high uniformity while scaling up and thickening. The layer number of both h -BN and graphene can be independently controlled by tuning the growth process. Furthermore, conductance measurements confirm that electrical hysteresis disappears on h -BN/Gr field-effect transistors, which is attributed to the h -BN dielectric surface. Our work blazes a trail toward next-generation graphene-based analog devices.